Teaching Metaphors Used in Sports Articles in French: A Case Study in a University Context - Ramírez, Sara Quintero; Arias Moreno, María Luisa (Didáctica. Lengua y Literatura, 2022)
The aim of this research is to present the result of an intervention with a group of fifth-semester students in the Bachelor´s Degree in Teaching French as a Foreign Language in the University of Guadalajara. The focus of the intervention was to make students analyze, understand, and use metaphors which are frequently used in the sports newspaper articles in French. The objective of our intervention was to apply a didactic sequence in which the students had to understand, analyze, and produce metaphors that are very frequently used in sports newspapers. With this study, we pretend to contribute to the studies focused on sports discourse, particularly those which analyze rhetorical figures as well as those centered on the teaching of foreign languages, mainly French.